RANCANG BANGUN SISTEM PRESENSI BERBASIS WEB - Lubis, Abwabar Rezkina Sapo (Jurnal Ilmiah Tenaga Listrik, 2021)
problem in itself in terms of practicality and data capture to the center. Especially if the attendance process is done manually by administrative officers, it will take quite a long time and are troublesome, and allow human errors to occur in the process of data recording to the center. Currently there are various applications of technological advances that have been created and are starting to replace conventional systems. One of them is the RFID (Radio Frequency Identification) system. The RFID system has now been widely used both as a security system device, checking goods, and as a medium for room access. This tool is designed by combining the work of a microcontroller with RFID technology in a system. Data in the form of a unique code from the RFID tag is used as student data. This system is tested using each block test, namely testing each function of the hardware used and testing the software in terms of functional specifications. The results of this study are an electronic student attendance recording system whose data is integrated with the Academic Information System to replace the manual student attendance recording model so as to reduce the occurrence of human errors in the centralized data recording process and reduce paper usage. And from this research, the distance to read the RFID reader is 2.5 cm long and works at a voltage of 3.3V.